It's all about the Team! - Teresa Lynch; Romy O'Callaghan (Teanga: The Journal of the Irish Association for Applied Linguistics, 2020)
In this paper, the authors consider issues relating to hearing interpreter teams, and deaf-hearing interpreter teams. A small-scale investigation of team interpreting in Ireland was conducted, considering where interpreters are working throughout Ireland and in what settings they are operating as a team. An anonymous survey was circulated to the interpreters of Ireland. From this it was observed that hearing interpreters tend to be the lead parties in organising interpreter teams. Furthermore it is interesting to note that Deaf Interpreters (referred to as DIs) report rarely working as part of a team. There is very little guidance for DIs, which further disadvantages them, as they cannot then easily advocate for their own position in the Irish context. The authors concluded by stating the need for guidance policies and/or toolkits surrounding how to decide who should be on an interpreter team. This would be beneficial for all interpreters, interpreting agencies and any organisation looking to book interpreters, whether they be public bodies or private sector.